Carcinoma of the breast with unusual clinical presentation: a case report - Settakorn J. (2014)
A common presentation of breast cancer is a palpable or non-palpable breast mass that might or might not demonstrate clinical signs of skin and/or nipple involvement. These malignant lesions frequently receive correct diagnosis only by physical examination under modestly experienced observers. We, hereby, reported the case of a 66-year-old woman who presented with a rapidly growing skin lesion at the left breast for three months. A 3.6x3x2.5 cm reddish, shiny, rubbery, sessile mass was seen on the upper outer quadrant of her left breast. The cytologic and histologic features of the tumor were typical for infiltrating ductal carcinoma. This case demonstrated a very unusual clinical presentation of breast cancer. No similar clinical feature of such cancer was mentioned in the reviewed literature.